Faktor-faktor Determinan Kepuasan Konsumen Pengguna Jasa Transportasi Laut (Studi pada Pengguna Jasa PT. Sinar Bahari Sakti Manado - Pelealu, Hendra (Universitas Sam Ratulangi, 2019)
Transportation is one of the important aspects in human life because transportation contributes greatly to life in relation to everyday human activities. The research sample is 100 consumer respondents of ships from PT. Sinar Bahari Sakti Manado. Using the factor analysis tool this study found that there were 4 (four) determinants of consumer satisfaction by users of sea transportation services, namely: 1) emotional factors, 2) product quality factors, 3) service quality factors, and 4) price factors. Based on these findings, it can be suggested that companies can improve the quality of their services, evaluate tariffs according to the benefits received by consumers, add product facilities, and conduct intensive promotions. Subsequent research needs to re-examine these factors both in the same or different studiesKeywords: Consumer Satisfaction, Factor Analysis